PENGGUNAAN BAHASA TABU DALAM UNGKAPAN PENDAKI GUNUNG LAWU - Shirin Ibadia, Yuninar; Widyastuti, Chattri Sigit (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
The purpose of this study is to analyze and describe the use of taboo language in expressions used by Mount Lawu climbers using a comparative historical linguistic approach. This type of research is qualitative descriptive research. The method of data provision utilized in this research is the observation method with free listening and note-taking techniques. Furthermore, data analysis uses referential method accompanied by comparative analysis technique. The result of this study shows that the dominant taboo language used by Mount Lawu hikers is taboo language concerning the issue of decency with the acquisition of (7 data), namely, taboo language of swearing type (4 data) and taboo language of curse type, sex, and body organs (1 data each). In addition, there are also expressions used in daily life related to taboo language which are related to urgent and unpleasant problems (3 data).